Factors Relating Work Performance of Village Health Volunteers in Narathiwat Province - Supapvanich, Chompunuch; Watae, Imron; Wanitchanon, Kamonwan (Princess of Naradhiwas University Journal, 2019)
This study aimed to determine work performance and study factors relating work performance of village health volunteers in Narathiwat province. This was a descriptive research and cross section study. A sample 169 village health volunteers working in Narathiwat province, received by using G*power program. Simple random sampling a method of lottery was used to select the study sample. The tool was self-reported questionnaires which received content validity (IOC = 0.91), reliability of support resources (conbach’s alpha = 0.88) and work performance (conbach’s alpha = 0.92). Data were analysed using descriptive statistics and Pearson correlation coefficient. The results showed that the village health volunteers gave average score of work performance in moderate level (= 2.26, SD = 0.38). Receiving supported things for work gave average score in good level (= 2.35, SD = 0.36). Furthermore, the factors including the receiving supervision (r = 0.244, p = 0.001) and training (r = 0.208, p = 0.007) and the community participation (r = 0.158, p = 0.040) were significantly correlated to the work performance of village health. The work performance of village health performance was in moderate level. According to this, the health care providers and the health care organization should support the health knowledge, training on health care services for village health performance, continuously. Furthermore, the participation of member in community or leader should help to support the better work performance of village health volunteer to serve people in community.